Rola prawa w zapewnianiu dostępności informacyjno-komunikacyjnej – wybrane zagadnienia - Mędrzycki, Radosław (Studia Prawa Publicznego, 2026)
This article attempts to demonstrate the primary role of the law in ensuring information and communication accessibility for people with disabilities in a democratic state governed by the rule of law. Information and communication accessibility is – alongside architectural accessibility and digital accessibility – one of the types of accessibility recognized under Polish law. In pursuit of the primary research objective, an attempt was made to identify the main sources of law governing accessibility at the international, supranational, and – most importantly – national levels. The issue at hand was addressed primarily from the perspective of administrative law, as it is administrative regulations that directly influence how public administration in Poland functions. The principles of promoting the common good and the administration’s obligation to comply with the law were also characterized as key general issues that influence the assurance of information and communication accessibility, albeit in a general way. The study employs a legal-dogmatic approach. The work is divided into five sections, titled as follows: Introduction; The axiological framework for ensuring accessibility; Primary legal sources governing accessibility; Selected determinants of information and communication accessibility; Conclusion and recommendations. The analysis confirms that the law is undeniably one of the key factors in the implementation of accessibility solutions within the Polish public administration. An attempt was made to demonstrate the impact of the Convention on the Rights of Persons with Disabilities and EU regulations on Polish law within the historical process of transforming Polish law. An important conclusion of the study is the finding that the values underlying accessibility, such as solidarity, do not constitute a sufficient legal basis for making public administration more accessible without specific legal solutions. Attention is also drawn to non-legal aspects, which, together with the law, ultimately shape accessibility in public administration.